Critical Link between Materials Chemistry and Cell-Level Design for High Energy Density and Low Cost Lithium-Sulfur Transportation Battery. Issue 6 (1st January 2015) - Eroglu, Damla; Zavadil, Kevin R.; Gallagher, Kevin G.
Abstract : A materials-to-system analysis for the lithium-sulfur (Li-S) electric vehicle battery is presented that identifies the key electrode and cell design considerations from reports of materials chemistry. The resulting systems-level energy density, specific energy and battery price as a function of these parameters is projected. Excess lithium metal amount at the anode and useable specific capacity, electrolyte volume fraction, sulfur to carbon ratio and reaction kinetics at the cathode are all shown to be critical for the high energy density and low cost requirements. Electrode loading is determined as a key parameter to relate the battery price for useable energy to the investigated design considerations. The presented analysis proposes that electrode loadings higher than 8 mAh/cm 2 (∼7 mg S/cm 2 ) are necessary for Li-S systems to exhibit the high energy density and low cost required for transportation applications. Stabilizing the interface of lithium metal at the required current densities and areal capacities while simultaneously maintaining cell capacity with high sulfur loading in an electrolyte starved cathode are identified as the key barriers for ongoing research and development efforts to address.